Chronic caffeine treatment enhances the resilience to social defeat stress in mice. Issue 2 (4th December 2014) - Yin, Yong-Qin; Zhang, Chun; Wang, Jian-Xin; Hou, Jia; Yang, Xu; Qin, Jing
Abstract : Strong evidence has shown that caffeine exerts antidepressant-like effects in chronic stress situations by increasing dopamine levels. Abstract : Strong evidence has shown that caffeine exerts antidepressant-like effects in chronic stress situations by increasing dopamine levels. However, whether caffeine mediates the dopaminergic system and interferes with the resilience to social defeat stress in mice is unknown. The aim of this study is to investigate the role of caffeine in the behavioral responses to social defeat stress and the possible regulatory role of the dopaminergic system. Mice experienced chronic social defeat stress for 10 days. Caffeine was administered intraperitoneally before, during and after social defeat stress. The time spent in interaction zone, social interaction ratio and sucrose preference test was used to measure the social avoidance and anhedonia in mice. The results showed that chronic pretreatment with caffeine for 14 days and for 10 days during stress reversed the avoidance of social behavior and anhedonia induced by social defeat stress in mice, suggesting the enhancement of the resilience to social defeat stress induced by caffeine. However, neither the treatment with caffeine only during the social defeat stress for 10 days nor the treatment with acute caffeine after defeat stress altered the resilience to stress. Furthermore, chronic caffeine treatment did not affect the normal locomotor activity and the desperate behavior in naïve mice. Moreover, the antagonism of dopamine D1 receptor and not D2 receptor reversed the effect of caffeine on the social avoidance and depressive-like behavior. Finally, pretreatment with higher doses of caffeine did not affect the behavioral response to social defeat stress. Taken together, our findings provide new insight into the effects of caffeine on social avoidance and anhedonia in mice. In addition, our results illustrated the value of measuring changes in depressive-like behavior before and after social defeat stress to determine the potential treatment of caffeine on depression through the regulation of dopaminergic system.